Correlation of Ultrasound with MRI for the Evaluation of Meniscal Tears - A, Suresh; Shetty, Aishwarya; Kala, Prachi (Asian Journal of Medical Radiological Research, 2019)
Background: Objective: To see the diagnostic value along with the sensitivity and specificity values of ultrasound in comparison to MRI for the evaluation of meniscal tears. Subjects and Methods: The study examined 70 patients who presented with history of trauma and suspected injury to the menisci. Patients were examined initially with ultrasound followed by non-contrast magnetic resonance imaging (MRI), with MRI used as a reference standard. Results: A total of 52 medial meniscal tears were detected on MRI out of which 42 cases were detected correctly on ultrasound giving a specificity of 80.8%; likewise, a total of 51 patients were detected with lateral meniscal tears on MRI out of which 38 cases were detected correctly on ultrasound giving a specificity of 74.5%. Conclusion: Ultrasound is a reliable imaging modality in identifying medial and lateral meniscal tears.